Cerebrovascular Pathology in Hypertriglyceridemic APOB-100 Transgenic Mice - Hoyk, Zsófia; Tóth, Melinda E.; Lénárt, Nikolett; Nagy, Dóra; Dukay, Brigitta; Csefová, Alexandra; Zvara, Ágnes; Seprényi, György; Kincses, András; Walter, Fruzsina R.; Veszelka, Szilvia; Vígh, Judit; et al. (Frontiers in Cellular Neuroscience, 2018)
Hypertriglyceridemia is not only a serious risk factor in the development of cardiovascular diseases, but it is linked to neurodegeneration, too. Previously, we generated transgenic mice overexpressing the human APOB-100 protein, a mouse model of human atherosclerosis. In this model we observed high plasma levels of triglycerides, oxidative stress, tau hyperphosphorylation, synaptic dysfunction, cognitive impairment, increased neural apoptosis and neurodegeneration. Neurovascular dysfunction is recognized as a key factor in the development of neurodegenerative diseases, but the cellular and molecular events linking cerebrovascular pathology and neurodegeneration are not fully understood. Our aim was to study cerebrovascular changes in APOB-100 transgenic mice. We described the kinetics of the development of chronic hypertriglyceridemia in the transgenic animals. Increased blood-brain barrier permeability was found in the hippocampus of APOB-100 transgenic mice which was accompanied by structural changes. Using transmission electron microscopy, we detected disruption of the brain capillary endothelial tight junction structure and edematous swelling of astrocyte end-feet. In brain microvessels isolated from APOB-100 transgenic animals increased Lox-1, Aqp4, and decreased Meox-2, Mfsd2a, Abcb1a, Lrp2, Glut-1, Nos2, Nos3, Vim, and in transgenic brains reduced Cdh2 and Gfap-σ gene expressions were measured using quantitative real-time PCR. We confirmed the decreased P-glycoprotein (ABCB1) and vimentin expression related to the neurovascular unit by immunostaining in transgenic brain sections using confocal microscopy. We conclude that in chronic hypertriglyceridemic APOB-100 transgenic mice both functional and morphological cerebrovascular pathology can be observed, and this animal model could be a useful tool to study the link between cerebrovascular pathology and neurodegeneration.